Effect of home-based self-supervised programs in healthy young adults - Muhammad Munir Sairi (2019)
Background: Balance is a precursor in the commencing of activities of daily living. However, limited studies have examined the effectiveness of training programs that are known to improve balance, in a home-based self-supervised setting. Purpose: This study examines and compares the effectiveness of home-based self-supervised strength training and proprioceptive training on quiet standing balance. Methods: 30 healthy young adults (16 females and 14 males) undergoing tertiary education were randomized into 3 treatments groups (PG: Proprioceptive Group, SG: Strength Training Group, CG: Control Group), and underwent a 4-week home-based self-supervised training program. Stabilometric analysis was carried out before and after the duration of training program. Results: There was a significant (p < 0.05) time effect for EO Bipedal: a-p range, a-p SD, m-l SD and 95CI, EC Bipedal: m-l range and m-l SD, a significant (p < 0.05) group effect for EO Dominant Leg Unipedal a-p range and SD, and a significant (p < 0.05) group x time effect on Eyes Open Dominant Leg Unipedal a-p RMS. However, all showed a decrease in balance capabilities with time, rather than an increase. Conclusion: The effects of home-based self-supervised strength and proprioceptive training program seem to be inconclusive. Future studies can perhaps implement effective adherence methods and also higher stimulus to elicit improvements in balance capabilities.